If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 17t + 15 = 11t + 51 Reorder the terms: 15 + 17t = 11t + 51 Reorder the terms: 15 + 17t = 51 + 11t Solving 15 + 17t = 51 + 11t Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '-11t' to each side of the equation. 15 + 17t + -11t = 51 + 11t + -11t Combine like terms: 17t + -11t = 6t 15 + 6t = 51 + 11t + -11t Combine like terms: 11t + -11t = 0 15 + 6t = 51 + 0 15 + 6t = 51 Add '-15' to each side of the equation. 15 + -15 + 6t = 51 + -15 Combine like terms: 15 + -15 = 0 0 + 6t = 51 + -15 6t = 51 + -15 Combine like terms: 51 + -15 = 36 6t = 36 Divide each side by '6'. t = 6 Simplifying t = 6
| 6y-15=-5y+18 | | (4n-1)(2n+4)= | | 4y+4=3y-6 | | 8x+3=13+3x | | (5a^2x+3ax^2-5x)+(2a^2x-5ax^2+7x)= | | 12x-10=62 | | -5(X+3)2(x-1)=-14 | | 8(2)+5= | | -9w-19=4w-6 | | -9-(4)(2)(x)=3249 | | 8x^2-21x+10=0 | | 8x^2-1x-9=0 | | 10w+16=10w+16 | | 3.2q-4.1-4.6q=-2.4q-3.2 | | 1+p+5+p=-2 | | 6r(2r-1)= | | 5x+24=12x+60 | | 6m+10=25-m | | 5x+11=12x+60 | | (5x^2-x-7)+(2x^2+3x+4)= | | 20e+50f=8(40) | | 22x-26x=10-14 | | -10-8x=-110+6 | | 3x-5y-4y+9x+2= | | 2xa-11=-5 | | 5x=48+2x | | (5x+3o)+9o= | | -3(4)+-2=x | | -(x-1)-4(x-3)=58 | | -0.2(-15x-10)=10 | | -7(4)+15=x | | z(2z-9)(z+4)=0 |